Large‐scale evaluation of physical drift and volatility of 2, 4‐D choline in cotton: a four‐year field study. Issue 8 (27th May 2022) - Hwang, Jeong‐In; Norsworthy, Jason K; Houston, Michael M; Piveta, Leonard B; Priess, Grant L; Zaccaro‐Gruener, Maria L; Barber, L Tom; Butts, Thomas R
Abstract: BACKGROUND: Cotton with resistance to 2, 4‐d choline, glufosinate and glyphosate allows over‐the‐top use of these herbicides for postemergence weed control. Nontransgenic cotton is highly responsive to low rates of 2, 4‐d, causing concern among farmers when the herbicide is applied near the crop. Injury to nearby cotton following application of 2, 4‐d choline is sometimes blamed on volatilization of the herbicide. RESULTS: A large‐scale experiment was conducted in 2018–2021 to better understand causes of damage to nearby sensitive cotton following an application of 2, 4‐d choline plus glufosinate‐ammonium. The herbicides were applied to 0.4 ha in the center of a 4‐ha non‐Enlist cotton field. At 30 min after application, air samplers were established in the treated center and outside the treated area in cardinal directions. The 72‐h cumulative air concentration of 2, 4‐d in the swath ranged from 3.3 to 7.1 ng m −3, and most volatile residues (5.0–25.5 ng m −3 ) were detected in samplers established in the downwind direction directly adjacent to the treated field. Cotton plants in three downwind transects that were covered for 30 min after application were not damaged by 2, 4‐d, whereas noncovered plants along the downwind transects were injured. No cotton injury occurred outside the treated area, except in the downwind direction during application even though wind direction changed after application. CONCLUSION: 2, 4‐d choline volatilizes, but findings show that the volatilization is not sufficient to damage cotton in the neighboring area following applications, pointing to the importance of applicators understanding wind direction/shift during the application along with proximity of sensitive crops in the downwind direction. © 2022 Society of Chemical Industry. Abstract : A herbicide 2, 4‐d choline can volatilize following application, but damage to neighboring sensitive cotton is most likely associated with physical drift in the downwind direction during application.